Adolescents' difficulties, strengths and feelings of insecurity: a cross-sectional descriptive survey in Finland - Kokkonen Pinja; Athanasopoulou Christina; Leino-Kilpi Helena; Puukka Pauli; Sakellari Evanthia (Switzerland, 2025)
The present study aimed to describe adolescents' self-reported emotional and behavioural strengths and difficulties, as well as their insecurity feeling. In addition, the aim was to examine the association with background characteristics, and explore the association between strengths and difficulties and insecurity factors. The study was conducted among 114 secondary school pupils in Finland, using an online questionnaire. Adolescents' emotional and behavioural difficulties and strengths, were mostly classified as normal. Strengths and Difficulties Questionnaire total score as well as internal and external score, were inversely associated with insecurity factors. Girls had significantly higher prosocial behavior compared to boys (P = 0.0007). The age of adolescents was found to be related to their internal difficulties (P = 0.02) and prosocial behavior (P = 0.01). Adolescent's perception of their family relations as poor was associated with external difficulties (P = 0.04). The current results, can be helpful for mental health professionals who work with adolescents in order to implement appropriate and needs specific mental health promotion interventions at individual but also community level. Finally, more research is needed to validate measures for insecurity. This will support mental health professionals in their clinical practice by providing them with all the important factors needed to support adolescents.